Genus Miltochrista (Lepidoptera, Erebidae, Arctiinae) from Laos, with description of one new species - Bayarsaikhan, Ulziijargal; Kwon, Hyung Wook; Kim, Jae Won; Bae, Yang-Seop (Zootaxa, 2025)
A new species, Miltochrista aurantia Bayarsaikhan & Bae, sp. nov. is described from Laos, and seven species, M. terminata (Moore, 1878), M. calamaria (Moore, 1888), M. quadrata (Holloway, 2001), M. kontumica (Dubatolov & Bucsek, 2013), M. simonka (Bucsek, 2014), M. lavides Volynkin, Černý & N. Singh, 2020, and M. tenuiprocessa Volynkin, Černy, Huang & Saldaitis, 2023, are newly recorded in this country. The previously unknown female genitalia of M. acteola (Swinhoe, 1903) and M. parvulus Bucsek, 2020, are studied for the first time. Illustrations of adults and genitalia of the examined species are provided with a list of known species of the genus from Laos.